Analysis of Household Income and Expenditure in Malaysia Using Principal Component Analysis and Maximum Likelihood Estimation - Atan, Alyaa Afza; Rusiman, Mohd Saifullah; Che Him, Norziha; Mislan, Muhammad Luqman Hakim (Enhanced Knowledge in Sciences and Technology, 2025)
The relationship between household income, expenditure, and economic stability has been the focus of extensive research due to its implications for policy and economic planning. This study examines the underlying factors influencing household income and expenditure in Malaysia using Principal Component Analysis (PCA) and Maximum Likelihood Estimation (MLE). The objectives of the research are to identify the primary factors influencing spending behaviour, examine the relationships among expenditure categories, and compare the performance of PCA and MLE. Key findings highlight the significant role of income variables and socio-demographic factors in shaping expenditure behaviour. PCA was employed to reduce dimensionality and highlight significant components, while MLE focused on parameter estimation. Results indicate distinct differences in cumulative variance explained by both methods, showcasing the strengths and limitations of each approach. These findings contribute to the development of targeted economic policies that address the needs of diverse households.